Tips on maximizing your running economy - Crowther, G. (2001)
In this article, author discusses some of the factors that affect running economy in hopes of helpingthe reader get as much mileage as possible out of his/her fuel. The importance of economy (that is the distance one can travel on a certain amount of energy/fuel) is underlined, the relations between economy and stride length as well as economy and stride length or economy and air resistance are shown. (This article originally appeared in the January 2001 issue of Northwest Runnermagazine.)